1996
DOI: 10.1046/j.1537-2995.1996.36896374373.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of red cell use in 45 hospitals in central Ontario, Canada

Abstract: This survey provides baseline blood transfusion information for a specific period that can help determine the need for hospital audits and maximum surgical blood-order schedule guideline reviews. This information is relevant to current recommendations to reduce patient's exposure to blood components. These transfusion data will assist in blood program planning based on known disease trends, demographics, and population changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 14 publications
5
66
1
1
Order By: Relevance
“…Two register-based studies from the US and Canada have evaluated red cell use per procedure or diagnosis. In a survey from Ontario, Canada, the red cells transfused to total knee, hip and ankle arthroplasty patients accounted for 5.1% of all red cells transfused in 1 year [20]. Friedman et al [18]reported that 3.5% of the transfused red cell units in the US went to patients admitted for bone and joint disease, excluding trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two register-based studies from the US and Canada have evaluated red cell use per procedure or diagnosis. In a survey from Ontario, Canada, the red cells transfused to total knee, hip and ankle arthroplasty patients accounted for 5.1% of all red cells transfused in 1 year [20]. Friedman et al [18]reported that 3.5% of the transfused red cell units in the US went to patients admitted for bone and joint disease, excluding trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 They only identified only a few studies that described overall utilization of red cells between and within different disciplines as well as patterns of use over time. 2,3,[24][25][26][27] There were also a significant number of studies describing red cell utilization in selected patient populations. In a 1992 survey conducted in 61 Toronto area hospitals, 65% of the allogeneic red cells used were administered to patients undergoing operative procedures categorized as digestive and abdominal, cardiovascular and musculoskeletal.…”
Section: Nadir Hemoglobin Levels Within Patient Groupsmentioning
confidence: 99%
“…In a 1992 survey conducted in 61 Toronto area hospitals, 65% of the allogeneic red cells used were administered to patients undergoing operative procedures categorized as digestive and abdominal, cardiovascular and musculoskeletal. 24 Brien et al 2 documented that 56% of all red cells were administered to surgical patients, while a study by Ghali 3 documented that 69% of red cells are transfused into surgical patients. In cardiac surgery, the proportion of patients receiving red cells ranges from 50% to 80%.…”
Section: Nadir Hemoglobin Levels Within Patient Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Helicobacter pylori infection predisposes patients towards peptic ulcer bleeding, as well as gastric lymphoma. Hemorrhage related to ulcers was a common cause of reported transfusions in some of the reviewed studies (21,23) and in descriptive studies (33,35). If receipt of transfusions because of H. pylori-induced ulcers can be linked to subsequent gastric lymphoma, adjustment for this risk factor would diminish any independent effect of transfusions.…”
Section: Exposure Assessmentmentioning
confidence: 99%